2007
DOI: 10.1227/01.neu.0000255334.95532.dd
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Dots Are Phagocytized by Macrophages and Colocalize With Experimental Gliomas

Abstract: Quantum dots are optical nanoparticles that, when delivered in nanomole doses, are phagocytized by the macrophages and microglia that infiltrate experimental gliomas. The optical signal may be detected, allowing for improved identification and visualization of tumors, potentially augmenting brain tumor biopsy and resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
76
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(81 citation statements)
references
References 29 publications
4
76
0
Order By: Relevance
“…We have shown that QDs or conjugated QDs accumulated inside the sinusoids in the liver and were subsequently phagocytosed by Kupffer cells. Our data were consistent with others' findings that QDs in the liver tend to be engulfed by macrophages (Jackson et al, 2007). However, when we deliberately depleted macrophages by clodronate liposomes, we still observed that QDs accumulated in the REScontaining organs with similar kinetics.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We have shown that QDs or conjugated QDs accumulated inside the sinusoids in the liver and were subsequently phagocytosed by Kupffer cells. Our data were consistent with others' findings that QDs in the liver tend to be engulfed by macrophages (Jackson et al, 2007). However, when we deliberately depleted macrophages by clodronate liposomes, we still observed that QDs accumulated in the REScontaining organs with similar kinetics.…”
Section: Discussionsupporting
confidence: 93%
“…It has been a consistent observation that systemic administration of pure, non-targeted QDs, and cell-targeted QDs, accumulates in substantial quantities in the liver, spleen, lymph nodes, and bone marrow in animal model systems (Ballou et al, 2004(Ballou et al, , 2007Gao et al, 2004;Cai et al, 2006;Jackson et al, 2007;Diagaradjane et al, 2008;Li and Huang, 2008). These organs all contain the RES system, where macrophage cells reside.…”
Section: Discussionmentioning
confidence: 94%
“…The electron micrographs also demonstrated that glioblastoma cell lineages internalize the QDs, expressing them The same process of tumor QD marking was described by Jackson et al, 30 wherein the nanocrystals were phagocytosed by macrophages and microglia, thus infiltrating experimental gliomas. Therefore, their study suggests the use of nonconjoined nanocrystals to assist the imaging system for surgical termination or glioblastoma tumor biopsies.…”
Section: Discussionsupporting
confidence: 70%
“…[19] Contrastingly, Jackson et al show intracellular sequestering. [20] Some decrease of intracellular QD occurred in vitro with KC (Fig. 2B).…”
mentioning
confidence: 86%